Pengaruh Brand Image Terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan Pada Produk Kosmetik MS Glow (Studi Pada Mahasiswi Fakultas Ekonomi dan Bisnis Universitas Trunojoyo Madura) - Hasanah, Nur; Kurriwati, Nirma (Jurnal Kajian Ilmu Manajemen (JKIM), 2025)
This research discusses the problems with one of the local cosmetic products in Indonesia, namely the MS Glow cosmetic product. The purpose of this study was to determine the effect of Brand Image on Customer Loyalty, to determine the effect of Brand Image on Customer Satisfaction, to determine the effect of Customer Satisfaction on Customer Loyalty, and to determine the effect of Brand Image on Customer Loyalty through Customer Satisfaction. This research uses a descriptive quantitative method. The analysis used in this research is path analysis. The data used in this study are primary and secondary data. Data collection techniques using a questionnaire with a total of 100 respondents. The results of this study are (1) Brand Image has a significant effect on Customer Loyalty, (2) Brand Image has a significant effect on Customer Satisfaction (3) Customer Satisfaction has a significant effect on Customer Loyalty and (4) Brand Image has an indirect effect on Customer Loyalty through Customer satisfaction.